2016
DOI: 10.1007/s11764-016-0563-2
|View full text |Cite
|
Sign up to set email alerts
|

Regret around fertility choices is decreased with pre-treatment counseling in gynecologic cancer patients

Abstract: Purpose Data have demonstrated an association between regret and lack of fertility counseling among patients undergoing treatment for non-gynecologic cancers. We sought to determine if fertility-related regret is reduced with pre-treatment counseling or fertility-sparing surgery (FSS) in patients with gynecologic cancers. Methods A cross-sectional survey was administered to 593 reproductive-age survivors (18-40 years old at diagnosis) of localized cervix, ovarian, or endometrial cancers that were eligible fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 22 publications
2
29
0
2
Order By: Relevance
“…This association was not apparent in the current study sample. Similarly, the data from the current study support the lower end of the range of previous reports regarding how often reproductive‐age women diagnosed with cancer receive fertility counseling (34%‐81%) . The low prevalence of fertility counseling in the current study sample (33%) may reflect practice differences in our geographically diverse sample .…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…This association was not apparent in the current study sample. Similarly, the data from the current study support the lower end of the range of previous reports regarding how often reproductive‐age women diagnosed with cancer receive fertility counseling (34%‐81%) . The low prevalence of fertility counseling in the current study sample (33%) may reflect practice differences in our geographically diverse sample .…”
Section: Discussionsupporting
confidence: 84%
“…Similarly, the data from the current study support the lower end of the range of previous reports regarding how often reproductive-age women diagnosed with cancer receive fertility counseling (34%-81%). [17][18][19][20][21][22][23][24][25][26] The low prevalence of fertility counseling in the current study sample (33%) may reflect practice differences in our geographically diverse sample. 15 Uptake of in vitro fertilization services also may vary based on state-mandated insurance coverage.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…Fertility preservation counseling is not only beneficial in assisting with treatment decision‐making, via lower decisional conflict or regret, but has a significant impact on emotional health. A systematic review has indicated that lack of fertility preservation counseling is associated with poorer quality of life and mental health outcomes .…”
Section: Psychological Supportmentioning
confidence: 99%